A QUANTITATIVE ANALYSIS OF SPATIAL ORGANIZATION OF THE URBAN CENTRES IN KASHMIR VALLEY – A GIS BASED STUDY USING PRIMACY INDEX, RANK SIZE RULE AND NEAREST NEIGHBOUR INDEX - Sameer Fayaz, M. S. Bhat, Zoya Naqshbandi (Journal of Experimental Sciences, 2016)
Kashmir valley located in the heart of huge mountain ranges has experienced urbanization over time and space and is presently home to 46 urban centres located in different parts of the region. The present study aims at analyzing the spatial distribution pattern and spacing of the towns using geographic information system (GIS) and the rarely used quantitative technique of near neighbour analysis. Kashmir Valley is characterized by the strong urban primacy of Srinagar city which is 8 times larger than the population of Anantnag town, 16 times larger than the population of Baramulla and 17 times larger than the population of Sopore town. The application of Rank Size Rule reveals that the relationship among the urban centres in Kashmir Valley is not in conformity with it. The study reveals that the urban settlements in Kashmir Valley are randomly distributed and do not exhibit any specific distribution pattern. The range of spacing varies from 33 kms to 3 kms. The average distance of spacing between the settlements is 9 kms, while the hypothetical mean nearest neighbour distance is 18 kms. The inferences of the analysis could be used as inputs for the spatial planning process and for balanced urban development.